Commitment of the Department of Environment and Hygiene in Waste Management : Komitmen Dinas Lingkungan Hidup dan Kebersihan dalam Pengelolaan Sampah - Nur Hidayah, Meisita; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and analyze the commitment of the Environmental and Hygiene Service of Sidoarjo Regency in managing waste and the factors constraining commitment to waste management carried out by the Sidoarjo Regency Environmental and Hygiene Service. This research is a qualitative descriptive study. This resource determination technique uses a purposive sampling technique, which consists of 1 Head of Waste Management, 1 staff of Cleanliness, 1 waste officer, and 3 community members. Data collection techniques were carried out by observation, interviews, and documentation. The data were analyzed by the method based on the concept of Milles and Hubberman. The results of this study indicate that: 1) The commitment of the Environmental and Hygiene Service (DLHK) of Sidoarjo Regency in the waste management program consists of three indicators of affective, normative, and continuity; 2) Constraints faced by the Environmental and Hygiene Service (DLHK) of Sidoarjo Regency in waste management, namely consistency and lack of budget.